A PILOT STUDY OF GROUP MINDFULNESS‐BASED COGNITIVE THERAPY (MBCT) FOR COMBAT VETERANS WITH POSTTRAUMATIC STRESS DISORDER (PTSD). Issue 7 (17th April 2013) - King, Anthony P.; Erickson, Thane M.; Giardino, Nicholas D.; Favorite, Todd; Rauch, Sheila A.M.; Robinson, Elizabeth; Kulkarni, Madhur; Liberzon, Israel
<x xml:space="preserve">Abstract</x> Background "Mindfulness‐based" interventions show promise for stress reduction in general medical conditions, and initial evidence suggests that they are accepted in trauma‐exposed individuals. Mindfulness‐based cognitive therapy (MBCT) shows substantial efficacy for prevention of depression relapse, but it has been less studied in anxiety disorders. This study investigated the feasibility, acceptability, and clinical outcomes of an MBCT group intervention adapted for combat posttraumatic stress disorder (PTSD). Methods Consecutive patients seeking treatment for chronic PTSD at a VA outpatient clinic were enrolled in 8‐week MBCT groups, modified for PTSD (four groups, n = 20) or brief treatment‐as‐usual (TAU) comparison group interventions (three groups, n = 17). Pre and posttherapy psychological assessments with clinician administered PTSD scale (CAPS) were performed with all patients, and self‐report measures (PTSD diagnostic scale, PDS, and posttraumatic cognitions inventory, PTCI) were administered in the MBCT group. Results Intent to treat analyses showed significant improvement in PTSD (CAPS (t(19) = 4.8, P < .001)) in the MBCT condition but not the TAU conditions, and a significant Condition × Time interaction (F[1, 35] = 16.4, P < .005). MBCT completers (n = 15, 75%) showed good compliance with assigned homework exercises, and significant and clinically meaningful improvement in PTSD symptom severity on posttreatment assessment in CAPS and PDS (particularly in avoidance/numbing symptoms), and reduced PTSD‐relevant cognitions in PTCI (self blame). Conclusions These data suggest group MBCT as an acceptable brief intervention/adjunctive therapy for combat PTSD, with potential for reducing avoidance symptom cluster and PTSD cognitions. Further studies are needed to examine efficacy in a randomized controlled design and to identify factors influencing acceptability and efficacy.